Discurso, persuasão e subjetividade : um estudo sobre os hiperbolismos paulinos - Aguiar, Adenilton Tavares de (2011)
This paper makes a study on the literary style of the apostle Paul, more precisely regarding the use of emphatic expressions in the homologoumena, i. e., the epistles whose authenticity is not denied in scholarship. The research seeks to establish points of contact between Theology, Linguistics and Religions Sciences. In the light of discourse analysis and by means of a bibliographical research in order to understand who was Paul his education in Tarsus, his personality, his training in Jerusalem, his life as Pharisee - , it is intended to assimilate the reasons which led the apostle to adopt a so peculiar and emphatic style than the other New Testament authors. Moreover, it is presented a new taxonomy for the four expressions categories analyzed, i. e., epauxesis, hyperthesis, hyperbole, and hyperoche. Such expressions were taken as subcategories of a figure of speech that we are calling hyperbolism. The paper is divided in three chapters: in the first one, it is discussed the intensity of the Pauline discourse based on the occurrence of compound verbs and adverbs of intensity; in the second, it is discussed the notion of emotionality in the Pauline discourse from the occurrence of hyperboles and self-exaltation expressions; in the third, it is sought to explain the reasons which led Paul to adopt an emphatic style. For now, it is concluded that it is not possible explain the frequent use of hyperbolism, along the homologoumena, in just one way. There are several issues involved, which do not exclude themselves, but are complementary